2011
DOI: 10.1016/j.jacc.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Tumors and Associated Arrhythmias in Pediatric Patients, With Observations on Surgical Therapy for Ventricular Tachycardia

Abstract: Clinically significant arrhythmias occurred in 24% of pediatric patients with cardiac tumors, VT being the most common type. Surgical excision for VT associated with rhabdomyomas and fibromas in selected patients is an important and effective management strategy in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
172
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(185 citation statements)
references
References 28 publications
3
172
0
10
Order By: Relevance
“…11 In addition, SEER includes only patients diagnosed with cancer before death, not postmortem findings. Although PMCTs commonly present with dyspnea, chest pain, palpitations, and edema, [11][12][13] they can also remain clinically silent until causing ventricular arrhythmias 13 and sudden cardiac death, 14 thus escaping inclusion in SEER. Nevertheless, more in line with our findings, a recent study in Grosseto's county in Italy (1998-2011) estimated the incidence of PMCTs at ≈130 per 100 million persons.…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, SEER includes only patients diagnosed with cancer before death, not postmortem findings. Although PMCTs commonly present with dyspnea, chest pain, palpitations, and edema, [11][12][13] they can also remain clinically silent until causing ventricular arrhythmias 13 and sudden cardiac death, 14 thus escaping inclusion in SEER. Nevertheless, more in line with our findings, a recent study in Grosseto's county in Italy (1998-2011) estimated the incidence of PMCTs at ≈130 per 100 million persons.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that cardiac metastatic tumors may result in complete atrioventricular block (11,12) and VT (13,14). Myocardium surrounded or infiltrated by metastatic tumor may manifest abnormal electrophysiological properties (15) and manifested as increased automaticity due to triggered activity, however, severity of myocardial infiltration surrounding the metastatic tumor was not homogeneous and resulted in complicated form of VT with variant ECG morphology and heart rate. The dominant activation pattern was irregular and randomly fluctuated between the anterior free wall and the septum of the RVOT.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Monomorphic ventricular tachycardia is one of the most frequently reported types of cardiac metastasis-related ventricular arrhythmia in both children and adults. [11][12][13][14] In contrast, polymorphic ventricular tachycardia (PMVT) in the setting of cardiac metastasis has been reported only once. 15 We describe an adult patient who presented with sustained PMVT as a manifestation of metastatic melanoma, and review the manifestations and consequences of cardiac involvement of melanoma.…”
Section: Introductionmentioning
confidence: 99%